2014
DOI: 10.4067/s0717-95022014000100024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la Percepción del Proceso de Enseñanza y Aprendizaje de un Curso de Morfología Humana por parte de Estudiantes de un Programa para Talentos Académicos

Abstract: RESUMEN:La alta capacidad intelectual se considera una manifestación diferencial del desarrollo cognitivo, siendo la estimulación temprana y sistemática favorecedores de su expresión y desarrollo. Es por ello, que otorgar oportunidades educativas enriquecidas es central para los los niños y niñas con talentos académicos. Esta investigación evalúa la percepción de los estudiantes frente a una metodología de enseñanza teórico-práctica en un curso dirigido a talentos académicos de enseñanza media (n=17) en el áre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Olivares et al (2014) found similar results when analyzing the perceptions of students who participated in a Chilean enrichment program: Students had a strong preference for interactive lessons and teaching practices that fostered flexibility.…”
Section: Community Voice and Engagement In Assessing Educational Pracmentioning
confidence: 60%
See 1 more Smart Citation
“…Olivares et al (2014) found similar results when analyzing the perceptions of students who participated in a Chilean enrichment program: Students had a strong preference for interactive lessons and teaching practices that fostered flexibility.…”
Section: Community Voice and Engagement In Assessing Educational Pracmentioning
confidence: 60%
“…Conejeros-Solar, Gómez-Arizaga, and Donoso-Osorio (2013), in a qualitative study on Chilean gifted students' perceptions about teacher characteristics, found that (a) students were able to conduct detailed assessments of their teachers; (b) students' perceptions were consistent with what other researchers have found about teacher effectiveness, such as practicality, flexibility, and pace; and (c) students also valued socio-emotional characteristics such as closeness, empathy, and trust. Olivares et al (2014) found similar results when analyzing the perceptions of students who participated in a Chilean enrichment program: Students had a strong preference for interactive lessons and teaching practices that fostered flexibility.…”
Section: Community Voice and Engagement In Assessing Educational Practicesmentioning
confidence: 60%
“…e use of big data has permeated all spheres of life thanks to the quick development of data technology. e use of big data in the eld of education has also received a lot of attention [6]. e use of big data is prevalent across all academic elds, with particular emphasis on computer software and applications, automation technology, macroeconomic management, mathematics, telecommunications technology, enterprise economy, and Internet technology.…”
Section: Introductionmentioning
confidence: 99%
“…Una de las estrategias para la enseñanza-aprendizaje de la morfología consiste en la orientación de sesiones teórico-prácticas. Las sesiones teóricas están orientadas a la adquisición e identificación del conocimiento morfológico, mientras que las prácticas incluyen la disección y el desarrollo de técnicas anatómicas, que se constituyen en una gran diversidad metodológica que fortalece la malla curricular (Olivares et al, 2014). Gracias a la implementación de las nuevas tecnologías, las herramientas pedagógicas que se emplean para la enseñanza de la morfología juegan un papel primordial en el proceso de enseñanza-aprendizaje, ya que facilitan la adquisición de los conocimientos de una forma rápida y efectiva, permitiendo menor cansancio mental y un aprendizaje ameno (Espín-Falcón et al, 2010).…”
Section: Marco De Referenciaunclassified